Bawaslu as Law Enforcer in Maintaining Democratic Elections in Indonesia - Manik, Anre; Siregar, Hisar (Golden Ratio of Data in Summary, 2025)
Regional Head elections in Indonesia are a real manifestation of direct democracy, where the people have a right to choose their regional leaders. The regional heads election is meant to be a very important thing in the discussion in society, where the regional heads election in Indonesia which is held every 5 (five) years is a momentum in determining who becomes the leader of the region. Often there are problems in regional head elections such as SARA issues, money politics to the issue of campaigns carried out outside the predetermined schedule. This makes the state through the law form an institution in terms of supervising regional head elections and elections. To overcome this, the existence of the general election Supervisory Agency (Bawaslu) as an independent supervisory institution is very crucial. In supervising the implementation of elections, ensuring that the democratic process rus fairly, honestly, and transparently. This journal will discuss the role of Bawaslu as a law enforcer in maintaining regional election democracy in Indonesia, focusing on the authority, challenges, and efforts made to increase the effectiveness of supervision.